2012
DOI: 10.3389/fncir.2012.00099
|View full text |Cite
|
Sign up to set email alerts
|

Modular Neuronal Assemblies Embodied in a Closed-Loop Environment: Toward Future Integration of Brains and Machines

Abstract: Behaviors, from simple to most complex, require a two-way interaction with the environment and the contribution of different brain areas depending on the orchestrated activation of neuronal assemblies. In this work we present a new hybrid neuro-robotic architecture based on a neural controller bi-directionally connected to a virtual robot implementing a Braitenberg vehicle aimed at avoiding obstacles. The robot is characterized by proximity sensors and wheels, allowing it to navigate into a circular arena with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 43 publications
(61 reference statements)
0
59
0
Order By: Relevance
“…The introduction of the tetanic stimulation (Cf. Procedure, point 7.2) improves significantly the distance travelled between two consecutive hits, thus improving the navigation performances of the robot 35 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the tetanic stimulation (Cf. Procedure, point 7.2) improves significantly the distance travelled between two consecutive hits, thus improving the navigation performances of the robot 35 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Both of these features present a problem: excessive synchronization will make it impossible to distinguish responses to stimuli from different electrodes, while cultures exhibiting epileptiform activity will respond to the first stimulus presented with a long outburst of activity, followed by a silent period, regardless of any successive stimuli delivered. Both these issues can be strongly ameliorated by the employment of patterned cultures 35 , in which the neural population is split into two or more weakly interconnected sub-groups.…”
Section: Discussionmentioning
confidence: 99%
“…Novellino et al (2007) developed a real-time neurorobotic system with a Khepera robot. Massobrio et al (2015); Tessadori et al (2012), also attempted a closed-loop system based on rat hippocampal neurons. Pizzi et al (2009) performed postprocessing using an artificial neural network of recordings from live neuronal cultures, while Takahashi et al (2016) suggested the usage of dissociated neural cultures as reservoir of dynamics.…”
Section: Proof-of-principle Of Embodied Bio-robotic Studiesmentioning
confidence: 99%
“…The possibility of using biological neurons grown on microelectrode arrays (MEAs) as part of robotic systems has been studied for approximately 15 years, see DeMarse et al (2001), Cozzi et al (2005), Novellino et al (2007), Warwick et al (2010b), Tessadori et al (2012). It is hoped that MEAbased robotics will address the well-known problem that robots based on conventional computer technology are not very good at adapting to surprising or unusual situations, see Tessadori et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that MEAbased robotics will address the well-known problem that robots based on conventional computer technology are not very good at adapting to surprising or unusual situations, see Tessadori et al (2012). One could compare the clumsy and Address(es) of author(s) should be given irregular movements of, e.g., most current vacuum cleaner robots to the rapid escape response through jet propulsion of the squid or the sophisticated wall-following behavior of the cockroach, see Dickinson et al (2000), Cowan et al (2014).…”
Section: Introductionmentioning
confidence: 99%